Factors Effecting Human Resource Practices on Employee Performance in Libya Oil & Gas Industry - Mohd Nasrun Mohd Nawi; Marwan Bashir S Eshtewi; Herman Shah Anuar (International Journal of Supply Chain Management, 2019)
The success of every organization depends highly on the human resources of the organizations. This is where the human resource has the skills, knowledge and competencies required for the execution of organizational strategy and planning. Many HRM studies have indicated positive effect of HR practices on employee performance, but there are some other studies that indicate the otherwise, indicating that the findings of the existing HRM studies are seemingly inconclusive. Equally, most studies are conducted in other contexts other in Libyan context, most especially in the context of Oil and Gas sector. Therefore, this study try to examine the effect of human resource practices (job design, training and development, compensation, performance appraisal and employee participation and communication) on employee performance in the Libyan oil and gas sector. Using the cross-sectional research approach, data were collected from a sample of 100 employees of Waha Oil Company (WOC). Multiple regression analysis technique will be used to test the studyâ€™s hypotheses. The results provided support for two out of the five hypotheses. The overall findings signified a positive effect of training development and performance appraisal on employee performance. This indicates thatÂ HR practices could have significant effect on performance, but the effect could be altered and modified by the contingent variables. The findings could also imply that the direct relationship between HR practices and performance could contain some mechanisms in-between. Lastly, the implications, limitations and suggestions for future research were discussed.